Ubiquitous multimedia computing - Li, Qing , 1971-; Shih, Timothy K. , 1961- (Chapman & Hall/CRC studies in informatics series, 2010)
Ubiquitous multimedia computing (ubi-media computing) brings together technologies for location/context adaptation, interdevice interaction/reaction, and media/data communication. One of the first to look at ubiquitous computing as applied to multimedia, this volume discusses the fundamental technologies and potential research in this cutting-edge area. It covers ubi-media computing from three levels: infrastructure, where fundamental technologies need to be developed; middleware, where integration of technologies and software systems needs to be defined; and applications, where usage cases in the real world need to be realized.